Can Preoperative Examination Help Choose the Best Surgical Procedure in Gastric Cancer? - Jia-Le Zhang; Zhen-Ning Wang; Hui-Mian Xu; Zhi Zhu; Bao-Jun Huang (Gastroenterology Research and Practice)
Aim. Gastrectomy with lymph node dissection is standard treatment in gastric cancer. This study aimed to explore whether preoperative investigation finds could predict lymph node metastatic scope in gastric carcinoma so that the optimal surgical procedure could be selected. Materials and Methods. Radical gastrectomy patients (n=378) were separated into two groups according to the lymph node metastatic scope. Univariate and multivariate analyses of preoperative examination results were performed to identify the predictors of metastatic scope. ROC curves were constructed, and the area under the curve (AUC) was calculated to estimate diagnostic values. Results. Serum CEA (OR: 3.73; 95% CI: 1.84–7.56; P≤0.001), tumor size (OR: 2.07; 95% CI: 1.08–3.98; P=0.03), and CT examination results (OR: 17.81; 95% CI: 9.18–34.55; P≤0.001) were identified as independent predictors. The AUC proved that they possessed significant diagnostic value. When CT examination was negative, the combination of serum CEA and tumor size showed high specificity (95.3%; 164/172), negative predictive value (92.7%; 164/177), and accuracy (89.0%; 170/191). Conclusions. Preoperative serum CEA, tumor size, and CT examination are independent predictors of lymph node metastatic scope and can be used for selecting the appropriate lymphadenectomy pattern in gastric cancer patients.